Evaluation of Participatory Leadership, Organizational Commitment, Organizational Culture on Teacher Retention Interest - Nela Budi Astuti; Syunu Trihantoyo; Ayu Wulandari (EDUJAVARE: International Journal of Educational Research, 2026)
Teacher retention is a strategic issue in educational human resource management because it affects the stability of school organizations and the sustainability of learning quality. Low teacher retention rates are often influenced by internal organizational factors, such as leadership style, level of organizational commitment, and the work culture that develops in the school environment. This study aims to determine how a leadership approach centred on participation, dedication to the institution, and values established by the institution influences a teacher's desire to continue working there. This study adopted a qualitative methodology through a descriptive framework, gathering information through comprehensive conversations with teachers who were specifically selected for their insights, reinforced by several observations and document review. Data analysis was conducted using a methodology that focused on condensing information, presenting relevant findings, and formulating conclusions using inductive reasoning. The results of the study indicate that participatory leadership can increase teacher retention interest through active involvement in decision-making and open communication. Organizational commitment acts as an internal reinforcement that encourages teachers to remain in their positions due to their emotional attachment and sense of responsibility towards the institution. In addition, a positive and supportive organizational culture creates a comfortable and meaningful work environment that strengthens teachers' desire to continue serving. This study enriches the theoretical framework of educational management studies and suggests practical steps that school administrators can take to create leadership and organizational management approaches that focus on maintaining a stable teaching staff over time